PENGARUH RASTRA TERHADAP KEMISKINAN DI ACEH - Sauma Ramadhana; Ferayanti Ferayanti; Cut Risya Varlitya (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract The RASTRA program is one of the programs to accelerate poverty reduction in cluster I, namely in the form of a family-based integrated social assistance program that touches the common people directly. This program is a tangible manifestation of Article 5 of the Presidential Regulation No. 15 of 2010 which regulates the program for accelerating poverty reduction. This study aims to determine the impact of the RASTRA program on poverty in Aceh in 2015-2018 using a descriptive quantitative approach. The results of the study show that if the RASTRA increases, it indicates that poverty in Aceh 2015-2018 is also high. Therefore, it is expected that the government can re-evaluate RASTRA RTS-PM Household Data.Keywords: RASTRA, Poverty, Aceh